Chemical Expansion and Change in Lattice Constant of Y‐Doped BaZrO3 by Hydration/Dehydration Reaction and Final Heat‐Treating Temperature. Issue 3 (12th February 2013) - Hiraiwa, Chihiro; Han, Donglin; Kuramitsu, Akiko; Kuwabara, Akihide; Takeuchi, Hisao; Majima, Masatoshi; Uda, Tetsuya
Abstract : Knowledge of thermal behavior of electrolyte is important for fuel cell fabrication. In this study, using high‐temperature X‐ray diffraction analysis (HT‐XRD) and thermo‐mechanical analysis (TMA), a systematic investigation of lattice constants was performed on Y‐doped BaZrO3, which is a promising candidate for electrolyte in protonic ceramic fuel cells. The results revealed that a chemical expansion was observed between 300°C and 450°C during the heating process in HT‐XRD, and was attributed to the dehydration of BZY. Furthermore, it was found that the lattice constants of the samples doped with Y, Sm, Eu, and Dy were larger for the ones finally heat‐treated at 1600°C for sintering than those heat‐treated at 1300°C for synthesizing. The similar behavior was not observed in Sc‐doped samples.